Transgenic ferritin overproduction enhances thermochemical pretreatments in Arabidopsis - Wei, Hui; Yang, Haibing; Ciesielski, Peter N.; Donohoe, Bryon S.; McCann, Maureen C.; Murphy, Angus S.; Peer, Wendy A.; Ding, Shi-You; Himmel, Michael E.; Tucker, Melvin P. (Biomass & bioenergy, 2015)
Reducing the severity of thermochemical pretreatment by incorporating iron ions as co-catalysts has been shown to enhance the sugar yield from dilute acid pretreatments and enzymatic saccharification. However, current approach of soaking iron containing acid solutions onto milled biomass prior to pretreatment is time-consuming and subject to diffusion limitations. Here, we overexpressed soybean ferritin protein intracellularly in Arabidopsis plants (referred to as FerIN) under the control of the 35S promoter for the purpose of accumulating iron ions in Arabidopsis plants. The transgenic Arabidopsis plants accumulated iron during growth under both normal and iron-augmented watering conditions. Prussian blue staining showed punctuate staining of iron predominantly on the interior surfaces of cell lumen in FerIN plants. The harvested transgenic biomass showed enhanced pretreatability, in that it released 13–19% more glucose and xylose than empty vector control plants. The data indicated a positive correlation between iron concentration and sugar release during pretreatment of transgenic biomass. •Ferritin protein intracellularly overexpressed in Arabidopsis, leading to iron accumulation.•Iron found to be mainly on lumenal surfaces of cell in transgenic plants.•Transgenic biomass had higher pretreatability.•Positive correlation exists between [Fe] and sugar release during pretreatment of biomass.